Wstępna ocena ryzyka zawodowego fizjoterapeuty za pomocą metody SWP = Preliminary evaluation of occupational risk for physiotherapists using the SWP method - Kulczycka, Kinga Dorota; Domagała, Marcin; Stychno, Ewa (Journal of Education, Health and Sport, 2016)
Kulczycka Kinga, Domagała Marcin, Stychno Ewa. Wstępna ocena ryzyka zawodowego fizjoterapeuty za pomocą metody SWP = Preliminary evaluation of occupational risk for physiotherapists using the SWP method. Journal of Education, Health and Sport. 2016;6(9):805-817. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159402 http://ojs.ukw.edu.pl/index.php/johs/article/view/3918 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. Wstępna ocena ryzyka zawodowego fizjoterapeuty za pomocą metody SWP Preliminary evaluation of occupational risk for physiotherapists using the SWP method Kinga Kulczycka, Marcin Domagała, Ewa Stychno Katedra i Zakład Zarządzania w Pielęgniarstwie Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie Chair and Department of Management in Nursing Faculty Health Sciences Medical University of Lublin Słowa kluczowe: Narażenie zawodowe, Fizjoterapeuci, Obciążenie pracą Key words: Occupational exposure, Physical therapists, Workload Dr n. med. Kinga Kulczycka, mgr. Marcin Domagała, dr n.med. Ewa Stychno Doctor of Medical Sciences Kinga Kulczycka, Holder of University Degree Marcin Domagała, Doctor of Medical Sciences Ewa Stychno Streszczenie Sposób wykonywania pracy, w warunkach znacznego obciążenia ma wielkie znaczenie w profilaktyce zaburzeń układu mięśniowo-szkieletowego. Praca fizjoterapeutów często wiąże się z koniecznością przyjmowania niefizjologicznych pozycji ciała, w trakcie których może dojść do urazów. Celem badania jest rozpoznanie pozycji ciała przyjmowanych przez fizjoterapeutów podczas pracy, które mogą stanowić czynniki ryzyka związane ze sposobem wykonywania pracy fizjoterapeuty. Materiał i metody Badania przeprowadzono w 2014 r. z udziałem 100 fizjoterapeutów pracujących na oddziałach rehabilitacji, na terenie województwa Świętokrzyskiego. Wyniki Respondenci oceniali jako niewłaściwe przyjmowane pozycje ciała, które zaobserwowali podczas wykonywania czynności zawodowych związane są z pochylaniem podczas wykonywania czynności, zgięcie odcinka lędźwiowego kręgosłupa i częste rotacje. Jako dodatkowe obciążenia w pracy uważali zginanie głowy do przodu lub skręcenie karku. Ruchy ramion stanowią znaczną uciążliwość dla fizjoterapeutów i występują podczas podnoszenia rąk do przodu i przesuwaniu ich w kierunku klatki piersiowej. Wnioski: świadomość ruchu, jego powtarzalność i dbanie o własne bezpieczeństwo powinno być kształtowane przez fizjoterapeutów w procesie edukacji oraz w trakcie praktyki zawodowej. Młodsi fizjoterapeuci i lepiej wykształceni częściej wybierają odpowiednie pozycje podczas wykonywania pracy. Wraz ze wzrostem liczby miejsc pracy wzrasta ryzyko urazu związanego z nieprawidłowym sposobem wykonywania czynności zawodowych. Summary The method of performing work in conditions of a considerable work load is of great importance in the prophylaxis of musculoskeletal disorders. The work of physiotherapists is frequently associated with the necessity for assuming non-physiological body positions, during which an injury may occur. The objective of the study is the recognition of body positions assumed by physiotherapists, which may be classified into occupational risk factors related with the method of performing the work of a physiotherapist. Material and method The study was conducted in 2014 in the Kielce Region and covered 100 physiotherapists employed in rehabilitation wards. Results The respondents evaluated as incorrect body positions assumed while performing occupational activities related with: long-term leaning position while performing activities, protrusion of the lumbar section of the spine, and frequent rotations. As an additional load at work they considered bending the head forward or twisting the neck. Arm movements constitute considerable onerousness for physiotherapists and occur while elevating the arms forward and moving them towards the chest. Conclusions: The awareness of movement, its repeatability, and care of own safety should be shaped by physiotherapists in the education process and during occupational practice. Younger physiotherapists more often choose adequate positions while performing work. An improvement of professional qualifications exerts an effect on assuming correct positions at work by physiotherapists. An increase in the number of workplaces is accompanied by an increased risk of injury related with incorrect method of performing occupational activities.